Retrieval Rate and Accuracy of Ultrasound-Guided 14-G Semi-Automated Core Needle Biopsy of Breast Microcalcifications - Yi, Jisook (The Korean Society of Radiology, 2014)
OBJECTIVE: To evaluate the retrieval rate and accuracy of ultrasound (US)-guided 14-G semi-automated core needle biopsy (CNB) for microcalcifications in the breast. MATERIALS AND METHODS: US-guided 14-G semi-automated CNB procedures and specimen radiography were performed for 33 cases of suspicious microcalcifications apparent on sonography. The accuracy of 14-G semi-automated CNB and radiology-pathology concordance were analyzed and the microcalcification characteristics between groups with successful and failed retrieval were compared. RESULTS: Thirty lesions were successfully retrieved and the microcalcification retrieval rate was 90.9% (30/33). Thirty lesions were successfully retrieved. Twenty five were finally diagnosed as malignant (10 invasive ductal carcinoma, 15 ductal carcinoma in situ [DCIS]) and five as benign. After surgery and mammographic follow-up, the 25 malignant lesions comprised 12 invasive ductal carcinoma and 13 DCIS. Three lesions in the failed retrieval group (one DCIS and two benign) were finally diagnosed as two DCIS and one benign after surgery. The accuracy of 14-G semi-automated CNB was 90.9% (30/33) because of two DCIS underestimates and one false-negative diagnosis. The discordance rate was significantly higher in the failed retrieval group than in the successful retrieval group (66.7% vs. 6.7%; p < 0.05). Punctate calcifications were significantly more common in the failed retrieval group than in the successful retrieval group (66.7% vs. 3.7%; p < 0.05). CONCLUSION: US-guided 14-G semi-automated CNB could be a useful procedure for suspicious microcalcifications in the breast those are apparent on sonography.